How Aging Affects Sleep-Dependent Memory Consolidation? - Harand, Caroline; Bertran, Françoise; Doidy, Franck; Guénolé, Fabian; Desgranges, Béatrice; Eustache, Francis; RAUCHS, Géraldine (Frontiers in Neurology, 2012)
Memories are not stored as they were initially encoded but rather undergo a gradual reorganization process, termed memory consolidation. Numerous data indicate that sleep plays a major role in this process, notably due to the specific neurochemical environment and the electrophysiological activity observed during the night. Two putative, probably not exclusive, models (“hippocampo-neocortical dialogue” and “synaptic homeostasis hypothesis”) have been proposed to explain the beneficial effect of sleep on memory processes. However, all data gathered until now emerged from studies conducted in young subjects. The investigation of the relationships between sleep and memory in older adults has sparked off little interest until recently. Though, aging is characterized by memory impairment, changes in sleep architecture, as well as brain and neurochemical alterations. All these elements suggest that sleep-dependent memory consolidation may be impaired or occurs differently in older adults. This review outlines the mechanisms governing sleep-dependent memory consolidation, and the crucial points of this complex process that may dysfunction and result in impaired memory consolidation in aging.